Research progress on the role of macrophages in acne and regulation by natural plant products - Zhao, Dan; Wang, Yun; Wu, Shuhui; Ji, Xiaotian; Gong, Ke; Zheng, Huie; Zhu, Mingfang (Frontiers in Immunology, 2024)
Acne vulgaris is one of the most common skin diseases. The current understanding of acne primarily revolves around inflammatory responses, sebum metabolism disorders, aberrant hormone and receptor expression, colonization by Cutibacterium acnes, and abnormal keratinization of follicular sebaceous glands. Although the precise mechanism of action remains incompletely understood, it is plausible that macrophages exert an influence on these pathological features. Macrophages, as a constituent of the human innate immune system, typically manifest distinct phenotypes across various diseases. It has been observed that the polarization of macrophages towards the M1 phenotype plays a pivotal role in the pathogenesis of acne. In recent years, extensive research on acne has revealed an increasing number of natural remedies exhibiting therapeutic efficacy through the modulation of macrophage polarization. This review investigates the role of cutaneous macrophages, elucidates their potential significance in the pathogenesis of acne, a prevalent chronic inflammatory skin disorder, and explores the therapeutic mechanisms of natural plant products targeting macrophages. Despite these insights, the precise role of macrophages in the pathogenesis of acne remains poorly elucidated. Subsequent investigations in this domain will further illuminate the pathogenesis of acne and potentially offer guidance for identifying novel therapeutic targets for this condition.